The independent value of a direct stenting strategy on early and late clinical outcomes in patients undergoing elective percutaneous coronary intervention. Issue 6 (12th February 2013) - Sardi, Gabriel L.; Laynez‐Carnicero, Ana; Torguson, Rebecca; Xue, Zhenyi; Suddath, William O.; Kent, Kenneth M.; Satler, Lowell F.; Pichard, Augusto D.; Lindsay, Joseph; Waksman, Ron
<x xml:space="preserve">Abstract</x> Objectives This study aimed to compare percutaneous coronary intervention (PCI) with direct stenting (DS) to balloon predilatation (PD) for patients undergoing elective PCI to determine whether there is an independent value for DS with regard to clinical outcomes. Background The safety of PCI with DS has been established, but the independent advantages of this technique are not entirely clear. Methods Patients undergoing elective PCI from January 2000 to December 2010 were included. The postprocedural and late clinical outcomes of 444 patients who underwent PCI with DS were compared with a propensity‐matched population of 444 subjects treated with PD. Results The two groups were well matched to 27 baseline clinical, procedural, and angiographic characteristics, thus allowing for a more accurate evaluation of the independent value of the stenting technique. Intravascular ultrasound was used in more than 60% of interventions in both groups. PCI performed with PD were longer (DS 45 ± 19.28 vs. PD 56 ± 23.72 minutes, P = 0.001), used more contrast (DS 154 ± 65.88 vs. PD 186 ± 92.84 cc, P = 0.001), and more frequently used balloon postdilation (DS 0% vs. PD 27.3%, P = 0.001). The incidence of periprocedural myocardial infarction (PPMI) was similar between DS‐ and PD patients (5.3% vs. 5.4%, P = 0.91). Likewise, the 1‐year rates of major adverse cardiac events (8.4% vs. 6.3%, P = 0.25), target lesion revascularization (3.9% vs. 2.5%, P = 0.24), and definite stent thrombosis (0.2% vs. 0.9%, P = 0.37) were similar among DS and PD patients, respectively. Conclusion During elective PCI, DS decreases overall procedure time and resource utilization, but fails to reveal an independent clinical advantage as there is no demonstrable benefit in regard to the incidence of PPMI, restenosis, or overall clinical outcomes up to 1‐year of follow‐up. © 2013 Wiley Periodicals, Inc.